2012
DOI: 10.3109/09513590.2012.683066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of serum FSH and estradiol on postmenopausal osteoporosis related to time since menopause

Abstract: Our study showed that neither FSH nor E2 has a strong impact on postmenopausal BMD. However it appears that time since menopause has a weak non-significant association with postmenopausal osteopenia and osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the Study of Women’s Health Across the Nation (SWAN), women who transitioned through menopause experienced a significantly higher rate of bone loss than women who remained premenopausal, independent of age [ 26 ]. In turn, a recent study suggests that time since menopause may have a stronger predictive value for low BMD in the lumbar and hip areas than did serum FSH or estradiol levels [ 27 ]. Data from the present study reinforces that idea, showing that women with more than 5 years since menopause had higher prevalence of osteoporosis, as well as lower BMD in all sites when compared to those with less time since menopause.…”
Section: Discussionmentioning
confidence: 99%
“…In the Study of Women’s Health Across the Nation (SWAN), women who transitioned through menopause experienced a significantly higher rate of bone loss than women who remained premenopausal, independent of age [ 26 ]. In turn, a recent study suggests that time since menopause may have a stronger predictive value for low BMD in the lumbar and hip areas than did serum FSH or estradiol levels [ 27 ]. Data from the present study reinforces that idea, showing that women with more than 5 years since menopause had higher prevalence of osteoporosis, as well as lower BMD in all sites when compared to those with less time since menopause.…”
Section: Discussionmentioning
confidence: 99%
“…This is an expression of the increasing domination of the resorption process over that of bone formation [ 11 ]. During the menopausal transition, a decline in ovarian activity and accompanying estrogen deficiency and increased follicle stimulating hormone (FSH), which overlaps with age-related changes, results in significantly increased bone turnover [ 12 , 13 , 14 ]. Bone loss increases two years before menopause and is at its highest level during the first 3 years of menopause, with losses reaching 3–5% annually [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen has a direct effect on osteoblasts, osteoclasts, and osteocytes [19][20][21]. There are studies that reported postmenopausal osteoporosis is associated with decreasing serum levels of estrogen [22]. Moreover, it was reported that serum level of estradiol has a strong relationship with osteoporosis and BMD [23].…”
mentioning
confidence: 99%